Novel cleavable cell‐penetrating peptide–drug conjugates: synthesis and characterization. (19th February 2014) - Lelle, Marco; Frick, Stefanie U.; Steinbrink, Kerstin; Peneva, Kalina
<x xml:space="preserve">Abstract</x> We report the first drug conjugate with a negatively charged amphipathic cell‐penetrating peptide. Furthermore, we compare two different doxorubicin cell‐penetrating peptide conjugates, which are both unique in their properties, due to their net charge at physiological pH, namely the positively charged octaarginine and the negatively charged proline‐rich amphipathic peptide. These conjugates were prepared exploiting a novel heterobifunctional crosslinker to join the N‐terminal cysteine residue of the peptides with the aliphatic ketone of doxorubicin. This small linker contains an activated thiol as well as aminooxy functionality, capable of generating a stable oxime bond with the C‐13 carbonyl group of doxorubicin. The disulfide bond formed between the peptide and doxorubicin enables the release of the drug in the cytosol, as confirmed by drug‐release studies performed in the presence of glutathione. Additionally, the cytotoxicity as well as the cellular uptake and distribution of this tripartite drug delivery system was investigated in MCF‐7 and HT‐29 cell lines. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.